Perbandingan Trapezius Squeezing Test dan Jaw Thrust Sebagai Indikator Kedalaman Anestesia pada Pemasangan Sungkup Laring - Hidayat, Jefferson; Sugiarto, Adhrie; Alatas, Anas (Majalah Anestesia dan Critical Care, 2016)
Manajemen jalan napas merupakan salah satu aspek penting dalam anestesiologi. Salah satu jenis alat bantu jalannafas yang sering digunakan adalah Laringeal Mask Airway (LMA/sungkup laring). Pemasangan sungkup laringtanpa pelumpuh otot membutuhkan kedalaman anestesi yang cukup. Trapezius squeezing test dan jaw thrustadalah dua uji klinis sederhana yang digunakan untuk menguji kedalaman anestesia. Penelitian ini bertujuan untukmembandingkan trapezius squeezing test dan jaw thrust sebagai indikator klinis menilai kedalaman anestesi padapemasangan sungkup laring dengan induksi anestesia menggunakan propofol. Sebanyak 128 pasien dirandomisasimenjadi dua kelompok yaitu kelompok 1 (kelompok jaw thrust) dan kelompok 2 (kelompok trapezius squeezingtest). Setelah premedikasi dengan midazolam 0,05 mg/kgBB dan fentanil 1 μg/kgBB, untuk induksi anestesiadiberikan propofol dosis titrasi. Manuver jaw thrust dan trapezius squeezing test dilakukan setiap 15 detik. Saatrespon motorik dari manuver hilang dilakukan pemasangan sungkup laring. Keberhasilan pemasangan padakelompok 1 dan 2 adalah 93,8% vs. 90,6% (p >0,05). Rata-rata penggunaan propofol pada kelompok 1 sebesar120,34 mg dan kelompok 2 sebesar 111,86 mg (p > 0.05). Pada kelompok 1 apnea dijumpai pada 10 pasien(15.6%) sedangkan pada kelompok 2 sebanyak 11 pasien (17.2%). Trapezius squeezing test sama baiknya denganjaw thrust sebagai indikator klinis dalam menilai kedalaman anestesia pada insersi sungkup laring. Kata Kunci: Jaw thrust, kedalaman anestesia, propofol, sungkup laring, trapezius squeezing test Airway management remains as one of the most important aspect in anesthesiology. Laryngeal Mask Airway(LMA) has been widely used as an airway device. Laryngeal mask insertion without muscle relaxant facilitationrequires an adequate anesthesia level. The purpose of this study was to compare trapezius squeezing test andjaw thrust maneuver as an indicator of anesthesia depth for laryngeal mask insertion, with propofol as inductionagent. There were 128 subjects who had been randomized into two groups: Group 1 (jaw thrust group) andGroup 2 (trapezius squeezing test group). All subjects received midazolam 0.05 mg/kg and fentanyl 1 μg/kg aspremedication. Propofol with titrated dose were used for anesthesia induction. Jaw thrust or trapezius squeezingtest maneuver were performed every 15 seconds in each group. When motoric responses were lost after maneuver,LMA was inserted. Succesfull LMA insertion were found in 93,8% patients (Group1) and 90,6% (Group 2) withp >0,05. Mean propofol consumptions were 120.34 mg in Group 1 and 111,86 mg in Group 2. Apnea was found in10 patients (15,6%) in Group 1 and 11 patients (17.2%) in Group 2. Trapezius squeezing test was as good as jawthrust maneuver as an adequate depth of anesthesia indicator for laryngeal mask insertion. Keywords: Departement of anesthesia, jaw thrust, laryngeal mask, propofol, trapezius squeezing test Reference Sood J. Laryngeal mask airway and its variants. Indian J Anaesth 2005;49(4):275–0. Verghese C, Berlet J, Kapila A, Pollard R. Clinical assessment of single use laryngeal mask airway the LMA Unique. Br J Anaesth 2006:80;677–9. Easley EH. The laryngeal mask airway: a review and update. J Clin Anaesth. 2005:16; 114–23. Cook TM. The classic laryngeal mask airway: a tried and tested airway. Br J Anaesth 2006; 96(2):149–52. Cressey DM, Claydon P, Bhaskaran NC, Reilly CS. Effect of midazolam pretreatment on induction dose requirement of propofol in combination with fentanyl in younger and older adult. Anaesth 2011;56:108–13. Towsend R. Jaw thrust as a predictor of insertion conditions for the proseal laryngeal mask airway. Anaesth 2009;20(1):59–62. Krishnappa S. Optimal anaesthetic depth for LMA insertion. Indian J Anaesth 2011;55(5): 504–7. Chang C. Comparison of the trapezius squeezing test and jaw thrust as indicators for laryngeal mask airway insertion in adults. Korean J Anesth 2011;61(3):201–4. Peacock JE, Lewis RP, Reilly CS, Nimmo WS. Effect of different rates of infusion of propofol for induction of anaesthesia in elderly patients. Br J Anaesth 1990;65:346–52. Peacock JE, Spiers SP, Mclauchlan GA, Edmondson WC, Berthoud BM, Reilly CS. Infusion of propofol to identify smallest effective doses for induction of anaesthesia in Yong and elderly patients. Br J Anaesth 1992; Stokes DN, Hutton P. Rate dependent induction phenomena with propofol: Implications for the relative potency of intravenous anesthetics. Anesth Analg 1991; 72:578–83. Scanlon P, Carey M, Power M. Patient response to laryngeal mask insertion after induction of anaesthesia with propofol or thiopentone. Can J Anaesth 1993;40:816–8. Katoh T, Suzuki A, Ikeda K. Electroencephalographic derivate as a tool for predicting the depth of sedation and anesthesia induced by sevoflurance. Anesthesiology 1998;88:642–50. Rudy N. Keefektifan trapezius squeezing test sebagai indicator kedalaman anesthesia saat pemasangan sungkup laring dihubungkan dengan bispectral index. Universitas Indonesia, 2012. Drage MP, Nunez J, Vaughn RS, Asai T. Jaw thrusting as a clinical test to assess the adequate depth of anaesthesia for insertion of the laryngeal mask. Anesth 1996; 51: 11667–70. Chang C. Optimal condition for laringeal mask airway insertion in children can be determinate by the trapezius squeezing test. J Clin Anaesth 2008;20:99–102. Reves GJ, Peter S.A, David AL, et al. Intravenous nonopiod anesthetics. In Miller’s Anesthesia. 7th ed. Philadelpia: Churchill Livingstone, 2010. p. 318–25. Morgan GA, Mikhail MS. Nonvolatile anesthetic agents: Clinical Anesthesiology. 4th ed. New York : McGraw-Hill, 2006. p.179–203 Hillier SC. monitored anesthesia Care. In: Barash’s. Clincal anesthesia. 5th ed. Philadelphia: Lippincott William & Wilkins, 2006. p . 2576–607.